2008
DOI: 10.1103/physrevlett.101.038302
|View full text |Cite
|
Sign up to set email alerts
|

Field-Induced Layer Formation in Dipolar Nanofilms

Abstract: Using molecular dynamics simulations, we demonstrate that the layering of confined colloidal particles with dipolar interactions, such as ferrofluids, in slablike geometries can be controlled by homogeneous external fields. For suitable surface separations, strong fields directed perpendicular to the film plane do not only align the particles but create additional layers in the system. The reverse effect occurs with an in-plane field which can induce a collapse of layers. Both effects are accompanied by pronou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
37
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 26 publications
5
37
0
Order By: Relevance
“…Moreover, extending the systems somewhat into the third dimension the lateral structures are supplemented by structure formation in vertical direction such as layering. This has been shown in recent experiments of ferrofluids [10] and related computer simulation studies [11,12].…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Moreover, extending the systems somewhat into the third dimension the lateral structures are supplemented by structure formation in vertical direction such as layering. This has been shown in recent experiments of ferrofluids [10] and related computer simulation studies [11,12].…”
supporting
confidence: 61%
“…Indeed, as we have recently demonstrated via Molecular Dynamics (MD) simulations for confined SM particles [11,12], external (homogeneous) magnetic fields directed parallel or perpendicular to the confining surfaces can "trigger" the formation or destruction of layers present in zero field. The surface separations where this becomes possible can be inferred from the location of maxima and minima of the normal pressure as function of the wall separation [11]. We also observed [12] interesting structure formation within the layers such as a hexagonal-like ordering in dense systems subject to parallel fields.…”
mentioning
confidence: 95%
“…7 In this work, it was shown that three new crystal structures, i.e., hexagonal-close-packed ͑hcp͒, body-centered-tetragonal, and body-centeredorthorhombic phases, can be stabilized by applying an external uniaxial field. For completeness, we mention that the behavior of colloidal particles with permanent dipole moments in external fields [8][9][10] and in confinement 11,12 has been widely investigated as well.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical [1][2][3], computer simulation [4][5][6][7][8][9], and experimental [10,11] studies have provided significant information about the orientational and spatial arrangement of dipolar particles in the vicinity of solid walls. The strongly anisotropic and long-ranged character of dipolar forces causes particular difficulties for the theoretical description of these systems.…”
Section: Introductionmentioning
confidence: 99%